2018
DOI: 10.1175/jcli-d-17-0342.1
|View full text |Cite
|
Sign up to set email alerts
|

Are Peak Summer Sultry Heat Wave Days over the Yangtze–Huaihe River Basin Predictable?

Abstract: The Yangtze–Huaihe River basin (YHRB) is the core region of sultry heat wave occurrence over China during peak summer [July and August (JA)]. The extremely hot and muggy weather is locally controlled by a descending high pressure anomaly connected to the western Pacific subtropical high. During 1961–2015, the heat wave days (HWDs) in JA over the YHRB exhibit large year-to-year and decadal variations. Prediction of the total number of HWDs in JA is of great societal and scientific importance. The summer HWDs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Meanwhile, previous studies on heat waves in eastern China, which is close to Korea, highlighted the role of North Atlantic Oscillation (NAO) in affecting heat waves through Rossby wave train that consists of successive high‐ and low‐pressure anomalies from North Atlantic Ocean to Eurasian continent (Gao et al, ; Sun, ). Moreover, Lee et al () recently reported that the high‐pressure cores of midlatitude zonal wave number 5 pattern coincide with regions of frequent occurrence of heat wave.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, previous studies on heat waves in eastern China, which is close to Korea, highlighted the role of North Atlantic Oscillation (NAO) in affecting heat waves through Rossby wave train that consists of successive high‐ and low‐pressure anomalies from North Atlantic Ocean to Eurasian continent (Gao et al, ; Sun, ). Moreover, Lee et al () recently reported that the high‐pressure cores of midlatitude zonal wave number 5 pattern coincide with regions of frequent occurrence of heat wave.…”
Section: Introductionmentioning
confidence: 99%
“…Yangtze River valley (YRV) is the core region for the occurrence of HW in China (Gao, Yang, et al, ). Many previous studies have widely addressed how HW events in this region are generated from the perspective of the anomalous large‐scale features of atmospheric circulation (e.g., Freychet et al, ) and anomalous boundary characteristics in observational diagnostics (Hu et al, ; Gao, Wang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the tropical Pacific, the anomalous warm SST is located in the central and eastern equatorial Pacific in early spring (Figure 9a), and evolves into the anomalous cold SST in mid‐summer (Figure 9b), which continues to enhance from summer to the following early winter (Figure 9c). This finding suggests that the decaying El Niño in early spring and the developing La Niña in summer promote positive SAT anomalies over the YRV through the enhancement and long‐term maintenance of the WPSH (Du et al ., 2009; Wu et al ., 2009; Xie et al ., 2009; Wang et al ., 2013; Gao et al ., 2018). On the other hand, SST anomalies in the North Atlantic present a meridional “warm‐cold‐warm” pattern similar to the North Atlantic tripole in early spring (Figure 9a).…”
Section: Evaluation Of the Predictability Sourcementioning
confidence: 99%